2019
DOI: 10.1186/s13030-019-0167-y
|View full text |Cite
|
Sign up to set email alerts
|

A potential relation between premenstrual symptoms and subjective perception of health and stress among college students: a cross-sectional study

Abstract: BackgroundA majority of women from all cultures and socioeconomic levels experience myriad symptoms known as premenstrual syndrome during the days prior to menstruation. The present study investigated commonly reported symptoms in the premenstrual phase among college students. The authors further scrutinized potential factors, including subjective perceptions of health, which may be related to the premenstrual-symptom constellation.MethodsWe conducted a cross-sectional survey, which included 200 participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 34 publications
(75 reference statements)
4
35
3
2
Order By: Relevance
“…Our investigation is in consistent with literature and it showed that pain intensity can be predicted by negative attitudes to menstruation among Iranian female population same as other nationalities ((35), (10). Pain intensity among menstruating females is different person by person, but there is a signi cant difference among individuals suffering intensive pain; because females with more negative attitudes to menstruation, undergo dysfunctions and disabilities caused by menstruating pain (4). Attitudes to menstruation is so much effective on precepted menstruating pain that females with more negative attitudes to menstruation can't pro t therapeutic goals of pain treatments (30).…”
Section: The Stanford Hypnotic Susceptibility Scalesupporting
confidence: 90%
See 2 more Smart Citations
“…Our investigation is in consistent with literature and it showed that pain intensity can be predicted by negative attitudes to menstruation among Iranian female population same as other nationalities ((35), (10). Pain intensity among menstruating females is different person by person, but there is a signi cant difference among individuals suffering intensive pain; because females with more negative attitudes to menstruation, undergo dysfunctions and disabilities caused by menstruating pain (4). Attitudes to menstruation is so much effective on precepted menstruating pain that females with more negative attitudes to menstruation can't pro t therapeutic goals of pain treatments (30).…”
Section: The Stanford Hypnotic Susceptibility Scalesupporting
confidence: 90%
“…The severity of symptoms can vary by individual and by month (5). PMS symptoms start 5 to 11 days before menstruation and normally go away while menstruation begins (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High-frequency HRV reduction is shown in PMS with depression [22]. College students have more negative health subjective perceptions and stress associated with the intensity of PMS [23]. Our study found that anxiety or depression increased the risk of PMS two-fold.…”
Section: Discussionmentioning
confidence: 48%
“…Additionally, in 2019, Matsumoto et al reported a higher prevalence of severe or extremely severe psychosocial symptoms among women who consider themselves "unhealthy and stressed" during their MC than among those who consider themselves "healthy and non-stressed" [6].…”
Section: Premenstrual Syndrome (Pms)mentioning
confidence: 99%